Search for novel diagnostic markers of chronic kidney disease in cats using proteome analysis - SHIMIZU, Momori (JOURNAL OF JAPANESE ASSOCIATION OF VETERINARY NEPHROLOGY AND UROLOGY, 2024)
Feline kidney disease is increasing in clinical practice. Staging of chronic kidney disease follows the criteria of the International Renal Interest Society (IRIS); i.e., based on plasma creatinine and symmetric dimethylarginine (SDMA). Plasma creatinine is affected by non-renal factors, including gender, age and muscle mass, whereas SDMA is known to increase after loss of >40% of glomerular filtration rate. In this study, we examined plasma glycoproteins as early diagnostic markers for chronic kidney disease and identified fucosylated apolipoprotein A-IV as such a marker.